Total Mikroba, Kekenyalan, dan Sifat Sensori Tahu Putih Berdasakan Perbedaan Lama Perendaman dalam Larutan Belimbing Wuluh - Reza Maulana; Nurrahman Nurrahman; Agus Suyanto (Jurnal Pangan dan Gizi, 2021)
White tofu is one type of tofu that is often consumed by the people of Indonesia. The process of making white tofu in Indonesia is generally still manual. White tofu has complete nutritional content so it is very easy to be contaminated by microbes. Microbial growth can be inhibited by using various methods, one of which is by giving a liquid with a low pH (acid) or by using flavonoid compounds, saponins, tannins and alkaloids. These compounds are contained in starfruit fruit so that it can be used to reduce the total microbes in white tofu. The value of the total number of plates that are safe in tofu according to the Food and Agriculture Organization is 1 x106 colon /gram. The general objective of the study was to determine the inhibition of starfruit solution against microbial growth, elasticity and sensory of white tofu. When immersion with star fruit solution concentration of 15% is 0, 2, 4, 6, and 8 hours. White tofu analyzed total microbial, elasticity, and sensory properties. The treatment has an influence on the total microbial, elasticity and sensory properties with the best value of 3.3 x105 colonies, elasticity 365.018 gf/mm or 3.577 N mm, and the average sensory test value of 3.05. The conclusion of the study of white tofu immersion with 15% starfruit solution showed a real difference, so that the best immersion treatment was immersion treatment for 4 hours.